Brain Peak Width of Skeletonized Mean Diffusivity (PSMD) and Cognitive Function in Later Life - Deary, Ian J.; Ritchie, Stuart J.; Muñoz Maniega, Susana; Cox, Simon R.; Valdés Hernández, Maria C.; Luciano, Michelle; Starr, John M.; Wardlaw, Joanna M.; Bastin, Mark E. (Frontiers in Psychiatry, 2019)
It is suggested that the brain’s peak width of skeletonised water mean diffusivity (PSMD) is a neuro-biomarker of processing speed, an important aspect of cognitive ageing. We tested whether PSMD is more strongly correlated with processing speed than with other cognitive domains, and more strongly than other structural brain MRI indices. Participants were 731 Lothian Birth Cohort 1936 members, mean age 73 years (SD=0.7); analytical sample was 656-680. Cognitive domains tested were: processing speed (5 tests), visuospatial (3), memory (3), and verbal (3). Brain-imaging variables included PSMD, white matter diffusion parameters and hyperintensity volumes, grey and white matter volumes, and perivascular spaces. PSMD was significantly associated with processing speed (-0.27), visuospatial ability (-0.23), memory ability (-0.17), and general cognitive ability (-0.25); comparable correlations were found with other brain-imaging measures. In a multivariable model with the other imaging variables, PSMD provided independent prediction of visuospatial ability and general cognitive ability. This incremental prediction, coupled with its ease to compute and possibly better tractability, might make PSMD a useful brain biomarker in studies of cognitive ageing.